Four Iron Age Silver Hoards from Southern Phoenicia From Bundles to Hacksilber - Eshel, Tzilla; Erel, Yigal; Gilboa, Ayelet; Šālêw, Śarîʾēl ca. 20./21. Jh.; Tirosh, Ofir; Yahalom-Mack, Naama (2018)
Iron Age silver in the Levant has attracted scholarly attention regarding its function as currency. Scholars debate whether hacksilber can be interpreted as representing a pre-monetary economic system, using pre-portioned silver exchanged in standardized weights, which inspired the invention of coins. In this study, four Iron Age silver hoards from southern Phoenicia (Tell Keisan, Tel Dor, 'Ein Hofez, and 'Akko) are examined from archaeological and analytical perspectives. The combination of a contextual analysis of the hoards, a typological study of the items in them, chemical analysis, and comparison with other Bronze and Iron Age southern Levantine hoards implies that the use of silver as currency changed throughout the Bronze and Iron Ages. In particular, contrary to common interpretations, the hoarding of silver in stamped bundles and the practice of hacking silver do not represent a single phenomenon. Rather, bundling was gradually replaced by the practice of hacking silver ingots to verify their quality. In Iron Age II, during every transaction, the hacked items were weighed using miniature silver items to balance the scales. We conclude that the "hacked silver" economic system was not based on "pre-weighing" and therefore cannot be defined as heralding the use of coins.
Keywords: Iron Age; Phoenicia; XRF; Currency; Forgery; hacked ingots; hacksilber; Hoards; mixing; Silver